2012
DOI: 10.1021/jm3002845
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Amidoximes that Act as Potent Inhibitors of Lysine-Specific Demethylase 1

Abstract: The recently discovered enzyme lysine-specific demethylase 1 (LSD1) plays an important role in the epigenetic control of gene expression, and aberrant gene silencing secondary to LSD1 dysregulation is thought to contribute to the development of cancer. We reported that (bis)guanidines, (bis)biguanides and their urea- and thiourea isosteres are potent inhibitors of LSD1, and induce the re-expression of aberrantly silenced tumor suppressor genes in tumor cells in vitro. We now report a series of small molecule a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…25 The crystal structure of LSD1/CoREST (PDB 2V1D) was prepared using PrepWizard, and SiteMap was then used to assess efficient binding within the LSD1 histone-binding pocket. Lowest energy conformers of 3D compounds were determined and docked in the LSD1 active site using Glide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The crystal structure of LSD1/CoREST (PDB 2V1D) was prepared using PrepWizard, and SiteMap was then used to assess efficient binding within the LSD1 histone-binding pocket. Lowest energy conformers of 3D compounds were determined and docked in the LSD1 active site using Glide.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and biological evaluation of other lead compounds identified in this screen have been previously published. 25 In the present study, two hits from the virtual screen, compounds 6 and 7 (Figure 1), were identified, and these compounds, as well as related analogues 8–20 , were purchased and evaluated (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Each compound was initially evaluated at a 10 μ M concentration, and an IC 50 value was determined for the most active peptide analogue 9 over a concentration range of 0.01–50 μ M. The known LSD1 inhibitor verlindamycin 3 6 was used as a positive control and produced 95% inhibition of the enzyme at 10 μ M. This level of inhibition is consistent with previously published values. 27,28 As shown in Table 1, all cyclic peptides inhibited the enzyme between 39 and 94%, following the relative rank order of 9 > 7 > 13 > 11 = 10 > 12 > 8 . Thus, the [Met] 4 H3 (1-21)-NH 2 cyclic peptide 9, in which the lactam bridge was between Lys5 and Glu10, produced the greatest LSD1 inhibitory activity, while cyclic [Lys2, Glu14] [Met] 4 H3 (1-21)-NH 2 8 displayed the least inhibitory activity.…”
mentioning
confidence: 95%
“…Apart from the polyamine analogues and guanidium compounds, Namoline is a small-molecule compound reported to inhibit LSD1 selectively over MAOs, although its potency is not high (IC 50 = 51 μM) 109 . Several research groups have developed other noncovalent LSD1 inhibitors 110-118 . The IC 50 values of some of these compounds are only in the micromolar range, however, inhibitors with submicromolar inhibitory potency have recently started to appear (Table 3).…”
Section: Introductionmentioning
confidence: 99%